Association between Provided Lifestyle Health Advice and Changes on Behavior of Diabetic Patients in Ramallah Governorate driven by Socioeconomic Factors - Fatemah Yaser Mahmoud Abu Abed (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Diabetes is responsible for about (25%) of deaths in adults aged 35 to 64 years across the Middle East region. Recent studies indicated that the prevalence of diabetes among Palestinians aged 20 to79 is approximately (20.6%), which is high in range compared to a worldwide prevalence of 6%, underscoring the urgent need for prevention and management through providing effective education programs. The study aims to assess the relationship between the provided lifestyle health advice in Ramallah government primary health clinics and the changes in diabetes health-related behaviors, driven by socioeconomic demographic factors.  In accordance to the provided health advice, the study found that (3.3%) received always and often advice in terms of smoking, (0.8%) of consuming healthy diet, (1.6%) of practicing physical activity similarly to adherence to medication. A statistically significant association was reported only between the diet advice provided by healthcare providers and eating healthy diet (p=.000; p=.000 respectively). On the other hand, age of participants showed a statistically significant difference across the level of delivered health advice respecting to smoking(p=.001), while gender & income affect the ability to receive health advice respecting to diet (p=.048; p=.03 respectively). Educational level & income affect the ability to receive health advice concerning physical activity (p=0.036; p=0.019 respectively). Level of education and the occupation of diabetic participants influenced the level of inquiring health advice regards medication (p=0.025; p=0.032). Health education at the primary level is considered essential for promoting health of diabetic patients by modifying risk factors concerning diet, physical activity, medication, smoking and alcohol consumption. Sociodemographic factors are integral part in understanding and improving these lifestyle behaviors. Initiating training programs for healthcare providers is significant to address the patients’ needs in the primary healthcare clinics, while launching a web-based educational platform, being accessible for patients could be helpful for enrichment of information.